EFFECTS OF LIGHT-EMITTING DIODES ON PLANTS. - Akmalbek Qadamov Alisherovich, (Ustozlar uchun, 2025)
This article explores the influence of light-emitting diodes (LEDs) on plant physiology, particularly in controlled environments such as greenhouses and vertical farms. By examining recent studies and experimental evidence, it identifies the optimal light wavelengths and intensities for promoting photosynthesis, growth, and flowering in various plant species. The article also compares LEDs with traditional lighting sources and discusses their potential in sustainable agriculture.